Some Remarks on Spectral Synthesis Sets - Joseph, J.; Muraleedharan, T. K. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
Relations between the difference spectra of unions and intersections are studied and their implications on some problems in spectral synthesis are observed.